Macmillan development project at the James Cook university hospital. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Walker, Jane; Hunter, Noeleen; Harris, Andrea; Nicholson, Alexander
Abstract : Background: National initiatives increase demand for health professionals with palliative care skills to improve patient experience, enhance patient quality outcomes and increase job satisfaction for staff working with complex clinical cases. Failure to recruit into a vacancy within the Trust's Specialist Palliative Care Team (SPCT) highlighted weaknesses in succession planning and poor development of skills within nursing establishment. Aims: To increase palliative and end of life care expertise in the nursing establishment. To improve education of peers To support the support governance agenda of palliative and end of life care including To support implementation of local and national guidelines. Method: Funding from Macmillan Cancer Support enabled recruitment for 2 years at a Band 6 level providing six possible 4-month secondments ('support sister') within the SPCT. Carefully structured training programmes were devised based on secondees' existing skills and linked to the KSF. Learning objectives included Increased knowledge of pain and symptom guidelines Improved understanding of referral to SPCT Improved liaison with community services Increased confidence in use of end of life care pathway and negotiating preferred place of care. Outcomes: Three nurses have completed secondments and all reported improved knowledge and skills. Two are now working in the SPCT, one as Macmillan Discharge Sister and one as Palliative Care Support Sister covering a colleague's reduced hours. Conclusion: The programme is on-going. While the first participants' reports of increased knowledge and confidence are encouraging, we plan assessment of impact back in the usual clinical team in the second phase of secondments. The project has supported recruitment to vacancies in the SPCT. The next phase will offer two 6-month opportunities since feedback indicates 4 months was slightly too short to consolidate all new learning.